Jeff Wall : a fotografia sonha! - Libardi, Carlos Alexandre de Mello (2018)
The text seeks to identify the work of contemporary photographer Jeff Wall as a break from formalist reductionism in a diachronic approach and ontological reductionism in a synchronic approach to classical photography. The staged and mnemic photograph of